Silicon nitride-based fiber monolithic ceramic and preparation method thereof
By wrapping the boron nitride interface layer on the surface of the silicon nitride fiber precursor and using wet spinning technology and hot press sintering process, silicon nitride-based fiber monolithic ceramics are prepared, which solves the problems of poor brittleness and fracture toughness of existing silicon nitride ceramic materials, and achieves high-strength and high-toughness ceramic materials.
Patent Information
- Application Number
- CN202411617473.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The poor brittleness and fracture toughness of existing silicon nitride ceramic materials limit their application in aerospace and other fields.
Silicon nitride-based monolithic ceramics were prepared by wrapping the boron nitride interface layer on the surface of the silicon nitride fiber precursor and using wet spinning technology and hot press sintering process. The process includes ball milling, drying, spinning, interface modification, pre-pressing molding and hot pressing sintering.
While maintaining the strength of the ceramic material, it significantly improves its fracture toughness, with bending strength and fracture toughness reaching 500~650 MPa and 10~16 MPa·m1/2 respectively, which is suitable for high-demand aerospace applications.
Smart Images

Figure CN119710982A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ceramic materials, and in particular relates to a silicon nitride-based fiber monolithic ceramic and a preparation method thereof. Background Art
[0002] Silicon nitride ceramic material is a typical nitride ceramic material, a functional and structural integrated ceramic material, which not only has functionality, such as good dielectric properties, uniform broadband transmittance, high temperature resistance, wear resistance, rain erosion resistance, good thermal shock resistance, etc., but can be widely used in petrochemical, metallurgical machinery, biomedicine, aerospace and other fields. Especially with the rapid development of aerospace in recent years, silicon nitride ceramic material has become one of the hot aerospace materials studied by scientific researchers. However, existing silicon nitride ceramics are often brittle and have poor fracture toughness, which greatly limits the application of silicon nitride ceramic materials. Summary of the invention
[0003] In view of the above problems existing in the prior art, the present invention provides a silicon nitride-based fiber monolithic ceramic and a preparation method thereof, which can improve the fracture toughness of the ceramic material while maintaining its strength.
[0004] To achieve the above object, the technical solution provided by the present invention is as follows:
[0005] In a first aspect, the present application provides a method for preparing a silicon nitride-based fiber monolithic ceramic, comprising the following steps:
[0006] S1: adding silicon nitride and a sintering aid into a solvent for ball milling, and then drying to obtain a ceramic powder;
[0007] S2: adding ceramic powder to the gel solution and ball milling to obtain a spinning solution, extruding the spinning solution through a spinning nozzle, and drying after solidification to obtain a silicon nitride fiber precursor;
[0008] S3: Dispersing flaky hexagonal boron nitride powder and nano-alumina powder in water, and ball milling to obtain an interface layer slurry; impregnating a silicon nitride fiber precursor into the interface layer slurry, and obtaining interface layer-modified silicon nitride fibers after drying;
[0009] S4: Arranging the silicon nitride fibers modified by the interface layer in a mold, maintaining the pressure at 10-20 MPa for 10-20 min, and obtaining a ceramic pre-pressed green body;
[0010] S5: After drying and debinding the ceramic pre-pressed green sheet, hot pressing and sintering are performed. Specifically, the hot pressing and sintering comprises placing the debinded ceramic pre-pressed green sheet into a sintering furnace, heating the pre-pressed green sheet to 1800-2000°C, applying a pressure of 25-30 MPa, and then maintaining the pressure and temperature for 1-2 h to obtain the silicon nitride-based fiber monolithic ceramic.
[0011] Optionally, during hot pressing sintering, the temperature is first raised to a first temperature, and then the load is gradually applied to 25-30 MPa and the temperature is simultaneously raised to 1800-2000°C; the first temperature is 1200-1600°C, and the heating rate during the process is 2-15°C / min.
[0012] Optionally, in S3, the mass fraction of boron nitride in the interface layer slurry is 6-10%, the mass fraction of aluminum oxide is 1.5-2.5%, and the immersion time is 5-10 minutes.
[0013] Optionally, the particle size of the flaky hexagonal boron nitride is 100-300 nm, and the particle size of the nano alumina powder is 5-30 nm.
[0014] Optionally, the thickness of the interface layer on the interface-layer-modified silicon nitride fiber is 5-15 μm.
[0015] Optionally, the gel solution in S2 is a 3-5% sodium alginate solution, the solvent of the sodium alginate solution is water or ethanol, and the diameter of the spinning nozzle used is 0.4-1 mm.
[0016] Optionally, the sintering aid in S1 includes aluminum oxide and yttrium oxide, and the ceramic powder includes the following raw materials in parts by weight: 90-95 parts of silicon nitride, 2-4 parts of aluminum oxide, and 3-6 parts of yttrium oxide.
[0017] Optionally, the coagulation method is: extruding the spinning solution into a calcium chloride solution at room temperature.
[0018] Optionally, the arrangement in S4 is a unidirectional arrangement or a cross arrangement.
[0019] Optionally, the debinding conditions are as follows: heating to 500-600° C. at a rate of 1-5° C. / min, and then maintaining for 1-2 hours.
[0020] Optionally, during hot pressing sintering, the temperature is first heated to 1200°C at a heating rate of 15°C / min, and then heated to 1600°C at a heating rate of 10°C / min; finally, pressure is gradually applied and the heating rate is maintained at 10°C / min to rise to 1800°C. When the temperature rises to 1800°C, the pressure is increased to 30 MPa and maintained at this temperature and pressure for 1 hour.
[0021] Optionally, the drying condition in S5 is: natural drying for 10 to 14 days.
[0022] On the other hand, the present application also provides a silicon nitride-based fiber monolithic ceramic, characterized in that it is obtained by the above-mentioned preparation method.
[0023] Optionally, the diameter of the silicon nitride cell of the silicon nitride-based fiber monolithic ceramic is 500-700 μm.
[0024] Compared with the prior art, this application has at least the following beneficial effects:
[0025] The present invention adopts 3-5% sodium alginate solution as gel solution, water or ethanol as solvent of sodium alginate solution, and mixed ceramic powder to obtain spinning stock solution, which is easier to extrude through spinning nozzle than other gel solutions such as polyethylene glycol butyral, and the extrusion is smooth and convenient.
[0026] The calcium chloride solution used in the present invention is used as the corresponding coagulation bath solution. The spinning stock solution is extruded into the calcium chloride solution at room temperature, which makes it easy for the silicon nitride ceramic powder and sintering aid powder stock solution extruded from the spinning nozzle to quickly coagulate into fibers, thereby improving the spinning efficiency. At the same time, the strength of the obtained fiber precursor is high, which is convenient for subsequent rapid pressing and molding.
[0027] The present invention combines wet spinning technology with the preparation process of silicon nitride ceramics, and gives the material excellent toughness while maintaining the strength of silicon nitride-based fiber monolithic ceramics. The bending strength and fracture toughness reach 500-650 MPa and 10-16 MPa·m respectively. 1 / 2 .
[0028] By wrapping the boron nitride interface on the surface of the silicon nitride fiber precursor after spinning, when subjected to external force, the cracks tend to extend at the boron nitride interface, absorbing a large amount of fracture energy, which is beneficial to the improvement of the fracture toughness of the material.
[0029] The diameter of the spinning solution extrusion process is controllable, easy to process, and has certain strength and toughness, which improves the strength and toughness of the fiber itself. Sodium alginate solution is used as the binder solution, which can be solidified at room temperature and has simple environmental conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The stability of the boron nitride interface layer slurry under the ball milling time in Example 1 of the present invention;
[0031] Figure 2 is a scanning electron micrograph of the silicon nitride fiber precursor in Example 1 of the present invention;
[0032] Figure 3 is the tensile strength of silicon nitride fiber precursors of different diameters in Example 2 of the present invention;
[0033] Figure 4 This is the microstructure of the silicon nitride-based fiber monolithic ceramic in Example 3 of the present invention. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0035] The experimental methods used in the embodiments of the present invention are conventional methods unless otherwise specified.
[0036] The reagents and materials used in this example can all be purchased conventionally. The quantitative experiments involved in the examples were repeated at least three times, and the results were averaged.
[0037] Raw material source: Silicon nitride particle size is 0.5μm.
[0038] Example 1
[0039] A method for preparing silicon nitride-based fiber monolithic ceramics comprises the following steps:
[0040] (1) Preparation of silicon nitride fiber precursor: First, 95 g of silicon nitride, 2 g of aluminum oxide, and 3 g of yttrium oxide were wet mixed, and anhydrous ethanol was used as the solvent for wet mixing. After silicon nitride, aluminum oxide, yttrium oxide, and anhydrous ethanol were mixed, they were mixed using a ball mill for 24 h, with a ball-to-material ratio of 1:2 and a rotation speed of 250 r / min. The wet mixed material was then dried using a rotary evaporator to obtain a uniformly mixed ceramic powder.
[0041] (2) Dissolve 5 g of sodium alginate in 95 g of deionized water and stir mechanically for 2 h to completely dissolve it in the deionized water to obtain a gel solution. Add ceramic powder to the gel solution at a mass ratio of 1:1 and ball mill for 24 h to obtain a uniformly mixed spinning solution. Use a 0.51 mm spinning nozzle to squeeze the spinning solution into a coagulation bath. At room temperature, the solution can be quickly formed in the coagulation bath and then pulled to obtain a silicon nitride fiber precursor. The scanning electron microscope image is shown in Figure 2 It can be found that the fiber surface is smooth and has no holes. The coagulation bath is a saturated calcium chloride solution, the diameter of the silicon nitride fiber precursor is 0.55 mm, and silicon nitride fiber precursors of different diameters are prepared by changing the diameter of the spinning nozzle.
[0042] (3) Interface modification: 6 g of 300 nm flake hexagonal boron nitride and 1.5 g of 30 nm alumina powder were mixed with 92.5 g of deionized water. The boron nitride interface layer slurry was evenly mixed using a ball mill for 3 h to obtain an interface layer slurry. The silicon nitride fiber precursor was immersed in the interface layer slurry for 20 min and dried after the immersion to obtain an interface layer-modified silicon nitride fiber. The thickness of the interface layer on the silicon nitride fiber was 14.73 μm.
[0043] During the experiment, the stability of the boron nitride interface slurry obtained by ball milling at different times was tested. The stability of the boron nitride interface slurry was characterized by the ratio of the liquid level height (H) of the boron nitride interface slurry after standing for 20 minutes to the initial liquid level height (H0) of the slurry before standing. The test results are shown in Figure 2. Figure 1 As shown, it can be seen that after 3 hours of ball milling, the liquid level of the interface layer slurry obtained is closest to the initial liquid level and has the best stability.
[0044] (4) Pre-pressing: The interface layer-modified silicon nitride fibers were cut into short fibers with a length of 50 mm and then arranged in the same direction in a graphite mold. A hydraulic press was used to pre-press at room temperature with a pressure of 20 MPa. After maintaining this pressure for 10 min, a ceramic pre-pressed blank was obtained.
[0045] (5) drying the ceramic pre-pressed green body naturally at room temperature for 10 days until the quality of the ceramic pre-pressed green body no longer changes, i.e., the drying process is completed;
[0046] The dried ceramic pre-pressed green body was debinded in a box-type resistance furnace, and the temperature was raised to 200 °C at a heating rate of 1 °C / min, and then raised to 500 °C at a heating rate of 2 °C / min, and kept at this temperature for 1 h before naturally cooling to room temperature;
[0047] The debinding green body was placed in a hot pressing sintering furnace for hot pressing sintering: the temperature was heated to 1200 ℃ at a heating rate of 15 ℃ / min, and the heating rate in the temperature range of 1200-1600 ℃ was 10 ℃ / min. When the temperature rose from 1600 ℃ to 1800 ℃, the pressure was gradually increased to 30 MPa, and finally maintained at 1800 ℃ and 30 MPa for 1 h. Finally, silicon nitride-based fiber monolithic ceramics were obtained, and its flexural strength and fracture toughness were 556.71 MPa and 15.37 MPa·m, respectively. 1 / 2 .
[0048] Example 2
[0049] A method for preparing silicon nitride-based fiber monolithic ceramics comprises the following steps:
[0050] (1) Preparation of silicon nitride fiber precursor: First, 92 g of silicon nitride, 5 g of yttrium oxide, 3 g of aluminum oxide and an appropriate amount of anhydrous ethanol were mixed together for wet mixing. The wet mixing process is to mix the raw materials with anhydrous ethanol and put them into a ball mill for 24 hours, with a ball-to-material ratio of 1:2 and a rotation speed of 250 r / min. The wet mixed powder is dried using a rotary evaporator to obtain a uniformly mixed ceramic powder.
[0051] (2) Mix 5 g of sodium alginate with 95 g of deionized water. After mechanical stirring for 2 h, the sodium alginate is completely dissolved in the deionized water to obtain a gel solution. Mix 100 g of the gel solution with 100 g of ceramic powder and ball mill for 24 h to obtain a spinning solution. At room temperature, the spinning solution is squeezed into a coagulation bath through a 0.58 mm spinning nozzle. The coagulation bath is a saturated calcium chloride solution. When the spinning solution enters the coagulation bath through the spinning nozzle, it can be formed within 20 seconds. After pulling, a silicon nitride fiber precursor with a diameter of 0.64 mm is obtained. Silicon nitride fiber precursors of different diameters can be prepared by changing the diameter of the spinning nozzle. The tensile strength of silicon nitride fiber precursors of different diameters can be seen in Figure 3 It can be seen that the fiber precursor prepared by the present invention has a high strength, which is convenient for subsequent arrangement and molding, as well as sintering after molding; and when the fiber diameter reaches a certain value, as the fiber diameter continues to increase, the strength decreases. When the fiber diameter is large, the defects introduced in the preparation process increase, causing the strength of the fiber to decrease.
[0052] (3) Interface modification: 8 g of flaky hexagonal boron nitride powder with a particle size of 200 nm and 2 g of alumina powder with a particle size of 10 nm were weighed and mixed with 90 g of deionized water, and the interface layer solution was ball milled for 3 h using a ball mill to obtain a uniformly mixed interface layer slurry. The silicon nitride fiber precursor was soaked in the interface layer slurry for 10 min, taken out and dried, and finally the interface layer-modified silicon nitride fiber was obtained, wherein the thickness of the interface layer on the silicon nitride fiber was 12.15 μm.
[0053] (4) Pre-pressing: The interface layer-modified silicon nitride fibers were first cut into short fibers with a length of 50 mm, and then placed in a graphite mold in a 0° / 90° cross-arrangement. The fibers were pre-pressed using a hydraulic press at a pressure of 15 MPa. The pressure was maintained at this pressure for 10 min to obtain a ceramic pre-pressed blank.
[0054] (5) drying the ceramic pre-pressed green body naturally at room temperature for 14 days until the quality of the ceramic green body no longer changes, i.e., the ceramic green body is dried;
[0055] The dried ceramic pre-pressed green body was debinded in a box-type resistance furnace. The temperature was first raised to 150 °C at a heating rate of 2 °C / min, then raised to 250 °C at a heating rate of 5 °C / min, and finally raised to 550 °C at a heating rate of 5 °C / min. The green body was kept at this temperature for 2 h, and then cooled to room temperature with the furnace after the end of the heat preservation.
[0056] The debinding green body was hot-pressed in a hot-pressing sintering furnace: the temperature was first raised to 800 °C at a heating rate of 15 °C / min, then raised to 1200 °C at 10 °C / min, and finally raised to 1800 °C at a heating rate of 5 °C / min. During the whole heating process, the pressure was gradually increased to 30 MPa, and maintained at 1800 °C and 30 MPa for 1.5 h. Finally, silicon nitride-based fiber monolithic ceramics were obtained, and their flexural strength and fracture toughness were 607.34 MPa and 14.21 MPa·m, respectively. 1 / 2 .
[0057] Example 3
[0058] A method for preparing silicon nitride-based fiber monolithic ceramics comprises the following steps:
[0059] (1) Preparation of silicon nitride fiber precursor: 92.5 g of silicon nitride, 2.5 g of aluminum oxide, 5 g of yttrium oxide and anhydrous ethanol were mixed and ball milled for 48 h to obtain a wet mixed powder, wherein the ball-to-material ratio was 1:2 and the rotation speed was 250 r / min. The wet mixed material was then dried using a rotary evaporator to obtain a ceramic powder.
[0060] (2) Dissolve 3 g of sodium alginate in 97 g of anhydrous ethanol and mechanically stir for 3 h to obtain a gel solution. Mix 100 g of the gel solution with 100 g of ceramic powder and continue ball milling for 24 h to obtain a spinning solution. Prepare silicon nitride fiber using wet spinning technology. Squeeze it into a saturated calcium chloride coagulation bath through a 0.84 mm spinning nozzle at room temperature and coagulate it in the coagulation bath for 3 h to obtain a silicon nitride fiber precursor. The diameter of the silicon nitride fiber precursor is 1.0 mm.
[0061] (3) Interface modification: 10 g of 100 nm flaky hexagonal boron nitride powder and 2.5 g of 30 nm alumina powder were dispersed in 87.5 g of deionized water and ball milled for 3 h to obtain an interface layer slurry. The silicon nitride fiber precursor was immersed in the interface layer slurry for 10 min and dried to obtain interface layer-modified silicon nitride fibers; the thickness of the BN interface layer was 10.26 μm.
[0062] (4) Pre-pressing: The interface layer-modified silicon nitride fibers were dried and pre-pressed using a hydraulic press. The fibers were first cut into short fibers with a length of 50 mm and then arranged unidirectionally in a mold for pre-pressing. The pre-pressing pressure was 20 MPa, and the ceramic pre-pressed blank was obtained by maintaining the pressure for 10 min.
[0063] (5) Drying the ceramic pre-pressed green body at room temperature for 14 days until the quality of the ceramic green body no longer changes, i.e., the drying is completed;
[0064] The dried green body is debinded in a box-type resistance furnace, and the box-type resistance furnace is heated to 600°C at a heating rate of 5°C / min and maintained for 1 h;
[0065] The debinding green body was hot pressed and sintered in a hot pressing furnace. The temperature was heated to 1200 °C at a heating rate of 15 °C / min. After the temperature reached 1200 °C, the pressure was increased and the temperature was heated to 1800 °C at a heating rate of 15 °C / min. At this time, the pressure was increased to 30 MPa. The temperature was kept at 1800 °C and the pressure was 30 MPa for 2 h to obtain silicon nitride-based fiber monolithic ceramics. The flexural strength and fracture toughness were 631.18 MPa and 11.37 MPa·m, respectively. 1 / 2 .
[0066] Table 1 Performance parameters of silicon nitride-based fiber monolithic structure ceramics
[0067] BN interface layer thickness (μm) Bending strength (MPa) <![CDATA[Fracture toughness (MPa·m 1 / 2 ).]]> Example 1 14.73 556.71 15.37 Example 2 12.15 607.34 14.21 Example 3 10.26 631.18 11.37
[0068] It can be seen from the above table that the silicon nitride-based fiber monolithic ceramic obtained in Example 1 has the highest fracture toughness, while the silicon nitride-based fiber monolithic ceramic obtained in Example 3 has the highest bending strength. This is related to the thickness of the BN interface layer. When the thickness of the BN interface layer increases, its bending strength decreases and the fracture toughness increases.
[0069] Figure 4 The microstructure of the silicon nitride-based fiber monolithic ceramic in Example 3, Figure 4 a is the cross-sectional morphology, from which it can be seen that the black phase is the silicon nitride cell and the gray phase is the boron nitride interface layer. The silicon nitride cell has a hexagonal structure, which is very beneficial to the mechanical properties of the ceramic. Figure 4 b is Figure 4 The enlarged view of the rectangular box in a, along Figure 4 Scan in the direction of the blue arrow in b to get Figure 4 c, it can be found that when the BN element content is the highest, the Si element content is the lowest, which indicates that the interface in the middle is BN.
[0070] The above are only preferred embodiments of the present invention, and the present invention is not limited to the contents of the embodiments. For those skilled in the art, various changes and modifications can be made within the scope of the technical solution of the present invention, and any changes and modifications made are within the protection scope of the present invention.
Claims
1. A method for preparing silicon nitride-based fiber monolithic ceramics, characterized in that: The steps include: S1: adding silicon nitride and a sintering aid into a solvent for ball milling, and then drying to obtain a ceramic powder; S2: adding ceramic powder to the gel solution and ball milling to obtain a spinning solution, extruding the spinning solution through a spinning nozzle, and drying after solidification to obtain a silicon nitride fiber precursor; S3: Dispersing flaky hexagonal boron nitride powder and nano-alumina powder in water, and ball milling to obtain an interface layer slurry; impregnating a silicon nitride fiber precursor into the interface layer slurry, and obtaining interface layer-modified silicon nitride fibers after drying; S4: Arranging the silicon nitride fibers modified by the interface layer in a mold, maintaining the pressure at 10-20 MPa for 10-20 min, and obtaining a ceramic pre-pressed green body; S5: After drying and debinding the ceramic pre-pressed green sheet, hot pressing and sintering are performed. Specifically, the hot pressing and sintering comprises placing the debinded ceramic pre-pressed green sheet into a sintering furnace, heating the pre-pressed green sheet to 1800-2000°C, applying a pressure of 25-30 MPa, and then maintaining the pressure and temperature for 1-2 hours to obtain the silicon nitride-based fiber monolithic ceramic.
2. The method for preparing silicon nitride-based fiber monolithic ceramics according to claim 1, characterized in that: During hot pressing sintering, the temperature is first raised to a first temperature, and then a load is gradually applied to 25-30 MPa and the temperature is simultaneously raised to 1800-2000°C; the first temperature is 1200-1600°C, and the heating rate during the process is 2-15°C / min.
3. The method for preparing silicon nitride-based fiber monolithic ceramics according to claim 1, characterized in that: In the interface layer slurry in S3, the mass fraction of boron nitride is 6-10%, the mass fraction of aluminum oxide is 1.5-2.5%, and the immersion time is 5-10 minutes.
4. The method for preparing silicon nitride-based fiber monolithic ceramics according to claim 1, characterized in that: The gel solution in S2 is a 3-5% sodium alginate solution, the solvent of the sodium alginate solution is water or ethanol, and the diameter of the spinning nozzle used is 0.4-1 mm.
5. The method for preparing silicon nitride-based fiber monolithic ceramics according to claim 1, characterized in that: The sintering aid described in S1 includes aluminum oxide and yttrium oxide, and the ceramic powder includes the following raw materials in parts by weight: 90-95 parts of silicon nitride, 2-4 parts of aluminum oxide, and 3-6 parts of yttrium oxide.
6. The method for preparing silicon nitride-based fiber monolithic ceramics according to claim 1, characterized in that: The coagulation method is: extruding the spinning solution into a calcium chloride solution at room temperature.
7. The method for preparing silicon nitride-based fiber monolithic ceramics according to claim 1, characterized in that: The arrangement in S4 is unidirectional arrangement or cross arrangement.
8. The method for preparing silicon nitride-based fiber monolithic ceramics according to claim 1, characterized in that: The debinding conditions are specifically as follows: heating to 500-600°C at a rate of 1-5°C / min, and then maintaining for 1-2 hours.
9. The method for preparing silicon nitride-based fiber monolithic ceramics according to claim 2, characterized in that: During hot pressing sintering, the temperature is first heated to 1200 ℃ at a heating rate of 15 ℃ / min, and then heated to 1600 ℃ at a heating rate of 10 ℃ / min; finally, pressure is gradually applied and the heating rate is maintained at 10 ℃ / min to 1800 ℃. When the temperature rises to 1800 ℃, the pressure is increased to 30 MPa and maintained at this temperature and pressure for 1 h.
10. A silicon nitride-based fiber monolithic ceramic, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Nitride ceramic-based wave-transparent composite material and preparation method thereof
CN114804891A
Method for Preparing Multichannel Ceramic Hollow Fiber Membrane
US20160137557A1
Method of manufacturing silicon nitride composition reinforced with silicon carbide whiskers having silicon oxide coating
US4855262A